OPTIMALISASI KEUNTUNGAN USAHA KULINER AYAM GEPREK MELALUI PENERAPAN METODE SIMPLEKS DALAM PEMOGRAMAN LINEAR - Avianus Pondaag; Divaria Kelen; Marcella Ontolay; Icandra Sitinjak; Vivienne Perutu; Jesen Waloni; Billy Jacob; James U. L. Mangobi (LPPM Politeknik Saint Paul Sorong, 2025)
This study aims to optimize profits for the culinary MSME business Ayam Geprek Warung Wifi in Tondano through the application of the simplex method in linear programming. The main problems faced are limited raw materials (chicken, flour, eggs) and uncertain demand, which result in production and profits not being maximized. Data were obtained from direct interviews with the business owner and literature studies. The analysis was conducted by modeling three production variables (Package A, B, and C) as an objective function to maximize profit with constraints on raw material availability. Calculations were carried out manually using a simplex table. he results of the study show that the optimal production combination is 10 units of Package C, 2.5 units of Package B, and no production of Package A. With this composition, the maximum profit that can be obtained is Rp1,262,500 per production period. It can be concluded that the simplex method can be effectively applied to support production decision-making in culinary SMEs, improve resource use efficiency, and achieve more optimal profits